Expanded criteria for retinopathy of prematurity screening in moderately preterm infants: Single‐center pilot study. Issue 11 (14th July 2016) - Yum, Sook Kyung; Moon, Cheong‐Jun; Youn, Young‐Ah; Lee, Jung Hyun; Kim, So Young; Sung, In Kyung
Abstract: Background: While developed countries seek to lower the gestational age and birthweight parameters in retinopathy of prematurity (ROP) screening, older, larger infants still develop ROP in other parts of the world. The aim of this study was therefore to define criteria to identify potential ROP developers who are outliers of the common screening range. Methods: A retrospective medical record review was performed in 147 inborn moderately preterm infants admitted to the neonatal intensive care unit during the study period. Univariate and logistic regression analysis was carried out. Results: Forty‐two infants developed ROP. Gestational age (31.4 ± 1.1 vs 32.4 ± 1.0 weeks, P  = 0.000) and birthweight (1607.7 ± 339.4 vs 1846.4 ± 317.2 g, P  = 0.000) were lower in those who developed ROP. Respiratory distress syndrome ( P  = 0.026) and documented sepsis ( P  = 0.003) were significant comorbidities on univariate analysis. Inotrope need >72 h starting in the first week of life ( P  = 0.004; OR, 5.181) and more than three transfusions of packed red blood cells ( P  = 0.028; OR, 3.891) were also significant, both on univariate and multivariate analysis. Conclusions: In moderately preterm infants, status should be evaluated in order to effectively select candidates for ROP screening without missing potential ROP developers.